ОРГАНИЗАЦИОННЫЕ МЕТОДЫ УПРАВЛЕНИЯ ПЕРСОНАЛОМ ВУЗА В УСЛОВИЯХ ИННОВАЦИОННЫХ ВНЕДРЕНИЙ - A. A. Aubakirov; M. A. Derbisaliev; A. A. Maltabarov (Экономика: стратегия и практика)
The purpose of this article is to substantiate the issue of the need to address the problem of resistance to changes on the part of employees (from top managers to ordinary employees) during the introduction of both the corporate governance system (CGS) and the development of the idea of diversifying income sources in higher educational establishments in Kazakhstan.The methodology of carrying out the work was ensured by studying and using the works of foreign scientists devoted to the topic of solving the problem of staff sustainability to changes. In addition, authors used the research materials of the company «France Telecom» in the framework of the topic under study.As the main results of the work should be highlighted the methods proposed by the authors to overcome the resistance of personnel to the process of organizational changes in universities in a changing environment.The results of this article can be applied in organizational approaches to managing changes in higher educational establishments.As the main conclusion of the article obtained on the basis of the results of the study, it is necessary to highlight the validity of the need to address the problem of staff sustainability to changes in Kazakhstan’s universities.